REWARD SYSTEM: A DETERMINANT OF EMPLOYEE PRODUCTIVITY - Maxwell Nwinye; Chimze Otto (Journals Park Publishing, 2025)
This study examined the relationship between reward system and employee productivity in money deposit banks, Port Harcourt, Rivers State. The researcher concentrated on remuneration, training and development as measures of reward system while task and contextual performance were considered as proxies of employee productivity. A survey research design was applied using purposive sampling method and structured questionnaire to collect data. Population size for the study was 202 employees selected from six money deposit banks. The sample size was 134 employees involving senior staff and supervisors in the banks. It was determined through Taro Yamane’s formula. Pearson Product-Moment Correlation was used to test the hypotheses. Both primary and secondary data were adopted for the study. The findings of the study disclosed that equitable remuneration, training and development of employees significantly enhance task and contextual performance. The researcher concluded that a well-structured rewards system effectively promotes employee productivity. It recommends that Banks should design policies and programs that guarantee regular training and development of employees to boost employee contextual performance.
Keywords: Reward system, Remuneration, Task performance, Employee productivity.